2019
DOI: 10.7150/jca.28320
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Preoperative Versus Postoperative Radiotherapy in Metastatic Rectal Cancer Treated With Definitive Surgical Resection of Primary Tumor: A Population Based, Propensity Score-Matched Study

et al.

Abstract: Preoperative chemoradiation followed by surgery has been recommended as a standard treatment for patients with stage II/III rectal cancer. However, the optimal sequencing of radiotherapy for metastatic rectal cancer remains unclear. Between 2004 and 2014, patients diagnosed with metastatic rectal cancer who underwent the resection of primary site and received radiotherapy were retrospectively selected using the Surveillance, Epidemiology, and End Results (SEER) database. The propensity score matching analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Both factors have been reported to correlate significantly independent of treatment with shorter OS in mCRC (56,57). On the other hand, the higher preoperative CEA levels and more patients undergoing direct surgeries presented in the subgroup without good oxaliplatin TRC are also negatively correlated with the survival of mCRC (58)(59)(60)(61). Therefore, when all patients carrying FA pathway mutations were considered as a whole in survival analyzes, the positive effect of chemotherapeutic response may have been compromised by other negative factors listed above, especially in small populations as in this study.…”
Section: A B Cmentioning
confidence: 96%
“…Both factors have been reported to correlate significantly independent of treatment with shorter OS in mCRC (56,57). On the other hand, the higher preoperative CEA levels and more patients undergoing direct surgeries presented in the subgroup without good oxaliplatin TRC are also negatively correlated with the survival of mCRC (58)(59)(60)(61). Therefore, when all patients carrying FA pathway mutations were considered as a whole in survival analyzes, the positive effect of chemotherapeutic response may have been compromised by other negative factors listed above, especially in small populations as in this study.…”
Section: A B Cmentioning
confidence: 96%
“…More important, the metastatic site seems to represent a malignancy with a different biological characteristics [7]. However, many studies analyzed metastatic rectal cancer as a whole without considering the metastatic site [8,9], which may provide an inaccurate conclusion.…”
Section: Ivyspringmentioning
confidence: 99%
“…Compared with postoperative CRT, neoadjuvant CRT had the advantages of improved resectability and local control, as well as less therapeutic toxicity 1 , 2 . Our previous study demonstrated that preoperative radiotherapy was superior to postoperative radiotherapy in terms of oncological outcomes in metastatic rectal cancer patients who received definitive surgical resection of the primary tumor 3 .…”
Section: Introductionmentioning
confidence: 99%